Marketing Communication Strategy of Chatime in Increasing Brand Awareness at Tzu Chi Hospital Jakarta - Mantu, Poppie Indriyanti; Al-Khorri, Alief Muhammad (MID Publisher International, 2026)
This study examines the marketing communication strategies implemented by Chatime Tzu Chi Hospital North Jakarta in increasing brand awareness. The rapid growth of the bubble tea beverage industry in Indonesia has intensified competition among brands, requiring companies to implement effective marketing communication strategies to attract consumers and strengthen brand recognition. Despite Chatime consistently receiving the Top Brand Award in the bubble drink category, understanding how its marketing communication strategies contribute to brand awareness at the outlet level remains important. Therefore, this study addresses the research question: How do marketing communication strategies implemented by Chatime Tzu Chi Hospital North Jakarta contribute to increasing brand awareness among consumers? Novelty: The novelty of this research lies in its qualitative exploration of integrated marketing communication strategies applied at the operational outlet level, providing insights into how advertising, sales promotion, public relations, personal selling, and direct marketing collectively influence brand awareness in the competitive bubble tea market. This study employed a qualitative research approach using a case study design. Data were collected through in-depth interviews, observation, and documentation involving key informants consisting of the assistant store manager, barista staff, consumers, and an academic expert in communication studies. The collected data were analyzed using descriptive qualitative analysis to identify the marketing communication strategies implemented and their influence on brand awareness. The findings indicate that Chatime applies integrated marketing communication strategies consisting of advertising, sales promotion, public relations, personal selling, and direct marketing to strengthen consumer awareness of the brand. Promotional programs and direct interaction between staff and customers were identified as key factors influencing consumer interest and brand recognition. The study concludes that integrated marketing communication strategies play an important role in increasing brand awareness and strengthening Chatime’s brand position within the competitive beverage market. These findings suggest that combining multiple promotional strategies and maintaining direct engagement with consumers can effectively enhance brand recognition and consumer loyalty.